Morphological and physiological plasticity in seedlings of Araucaria angustifolia and Cabralea canjerana is related to plant establishment performance in the rainforest - Olguin, Flavia Y.; Moretti, Ana Paula; Pinazo, Martin Alcides; Gortari, Fermín; Vera Bahima, José; Graciano, Corina (Elsevier, 2020)
High phenotypic plasticity is an important characteristic that should have a tree species that is going to be used to restore degraded rainforests, as those are stressful and changing environments. Quantifying phenotypic plasticity is necessary to compare species and populations. At least 17 different indexes have been employed to measure phenotypic plasticity and most of them were analyzed in pot experiments. However, no studies that evaluate the degree of coincidence between plasticity indexes were applied in pot and field experiments. The aim of this work is to determine the importance of species acclimation and plasticity to the establishment of planted trees for rainforest restoration. We estimated and compared the plasticity and robustness in plants of Araucaria angustifolia and Cabralea canjerana acclimated to full sun and canopy shade in pots, with the slope of the reaction norm. Then, we described the plasticity in a continuum of coverage gradients in rainforest gaps, with environmentally standardized plasticity index for individual distances (ESPIid). Finally, we analyzed the relationship between plasticity and growth performance. C.canjerana had higher plasticity and robustness than A.angustifolia, both in the pot experiment and in the gap experiment. The light-demanding species had lower plasticity than the intermediate shade-tolerant species. The slope of the reaction norm and the ESPIid gave similar qualitative results in the comparison of the species. In C.canjerana, the trait with higher plasticity in the gaps was specific leaf area, which was the better predictor of height 42-months after planting. On the other hand, the prediction of A.angustifolia growth was better fitted with incident light. Growth in A.angustifolia, a species with low plasticity, can be predicted with environmental variables, while growth in C.canjerana, a species with high plasticity, is better predicted with plant traits. The species with higher plasticity in morpho-physiological traits established in all the microenvironments within the gaps, with high growth rate. Survivor of the species with low plasticity was lower in shaded microenvironments than in the positions with higher radiation and lightlimited its growth in the gaps. Knowing the plasticity and acclimation capacity of the native species is crucial to choose the better places to plant trees in rainforest restoration and to enhance performance of the young plants.